Microneedle Patches as Drug and Vaccine Delivery Platform - Li, Junwei; Zeng, Mingtao; Shan, Hu; Tong, Chunyi (Current Medicinal Chemistry, 2017)
Background: Transcutaneous delivery is the ideal method for delivering therapeutic reagents or vaccines into skin. With their promise of self-administration, cost-effective and high efficiency, microneedle patches have been studied intensively as therapeutic and vaccination delivery platform that replaces injection by syringe. This review aims to summarize the recent advancements of microneedle patches in application for drugs and vaccine delivery. Methods: We reviewed the most of recently published papers on microneedle patches, summarized their evolution, classification, state-of the-art capabilities and discussed promising application in drugs and vaccine delivery. Results: With the rapid development of nanotechnology, microneedle patches have been improved by switching from undissolving to dissolving microneedles, and their safety has also improved dramatically. As a drug delivery tool, microneedle patches can deliver bioactive molecular of different physical size. Additionally, microneedle patches can be coated or encapsulate with DNA vaccine, subunit antigen, inactivated or live virus vaccine. Combining clinical results with the results of patient interview, microneedle patches are found to be feasible and are predicated to soon be acceptable for the medical service. Conclusion: In this review, we summarized the evolution, current and future application of microneedle patches as delivery vehicle for drugs and vaccines. Compared with traditional delivery tools, microneedle patches have many advantages, such as providing pain-free, non-invasive, convenient route for reagent administration and delivery, with no cold chain required for storage and transportation as well as decreasing sharp medical waste, needle-caused injury and transmission of blood-borne infectious disease in rural area. However, even though there are dramatic progress in preclinical investigation of microneedle patches, further testing will be required for clinical application. Further research should be implemented in multiple fields, such as vaccinology, immunology, and materials science, to improve this delivery platform. Because of their advantages in dose sparing, safety and treatment compliance, microneedle patches are expected to be widely applied in clinical treatment and vaccine administration in near future.
Keywords: transcutoneous delivery